Background Report on Access, Equity, Excellence, and Finance in Higher Education in Bihar - World Bank (World Bank, Washington, DC, 2017)
This background report was written at a time when the Government of Bihar (GoB) was launching a number of reforms in higher education. A private universities bill passed the Bihar state assembly in April 2013 paving the way for opening of private universities in the state. A strong effort to encourage universities and colleges to obtain National Assessment and Accreditation Council (NAAC) accreditation has been initiated. The objective of this background report is to provide policy-makers and stakeholders in higher education in Bihar with an overview of the opportunities and challenges that the state is facing in terms of reaching the ambitious goals in mission manav vikas. The report analyzes the data and information which is readily available on the access, equity, excellence, and finance. It can also be used as a baseline for the state higher education plan in Bihar drafted as part of the Rashtriya Uchchatar Shiksha Abhiyan (RUSA) process. The report is reflecting what has been possible to do in a short period of time with the available data and information.